Depicting protracted refuge. Postcards from a refugee camp - Neto, Pedro Figueiredo (2021)
This essay confronts the viewer with protracted refuge by looking at the Meheba Refugee Camp, Zambia. Created in 1971 and still running well beyond the moment of emergency at its origin, Meheba challenges the generic and generalized visual representation of refugees and refugee camps. This photo-essay seeks to depict how displaced populations forge a life in exile in spite of all the adversities, but also of how the spaces of refuge evolve, consolidate, and become part of the territory in which they are located.